Coping strategies between gender, academic streams and age groups in a sample of Singaporean adolescents - Krishnan Thamarai Kanni. (2008)
This study presents data on the ways a sample of Gan Eng Seng School pupils choose to cope with their problems and the effectiveness of the school support system in meeting the needs of the pupils. A sample of 151 pupils from Secondary One and Three, Express and Normal (Academic) streams completed the Adolescent Coping Scale (ACS: Frydenberg and Lewis, 1993) which yields data on eighteen potential coping scales. Forty pupils -five girls and five boys from each stream and each level were picked on a random basis for an in-depth interview that comprised a series of questions on three areas of concern - family, school and peers. The association between coping styles and gender, academic streams and age were studied. The school support system- the Pupil Welfare Department and its programmes- were also assessed to evaluate its effectiveness and the pupils' perception of it as a possible source of support in meeting their coping needs.